Mid-air - Williams, Alicia, 1970- (Atheneum Books for Young Readers, an imprint of Simon & Schuster Children's Publishing Division, 2024)
A tender-souled boy reeling from the death of his best friend struggles to fit into a world that wants him to grow up tough and unfeeling. It's the last few months of eighth grade, and Isaiah feels lost. He thought his summer was going to be him and his boys Drew and Darius, hanging out, doing wheelies, watching martial arts movies, and breaking tons of Guinness World Records before high school. But now, more and more, Drew seems to be fading from their friendship, and though he won't admit it, Isaiah knows exactly why. Because Darius is...gone. A hit and run killed Darius in the midst of a record-breaking long wheelie when Isaiah should have been keeping watch, ready to warn: "CAR!" Now, Drew can barely look at Isaiah. But Isaiah, already quaking with ache and guilt, can't lose two friends. So, he comes up with a plan to keep Drew and him together--they can spend the summer breaking records, for Darius. But Drew's not the same Drew since Darius was killed, and Isaiah, being Isaiah, isn't enough for Drew anymore. Not his taste in clothes, his love for rock music, or his aversion to jumping off rooftops. And one day something unspeakable happens to Isaiah that makes him think Drew's right. If only he could be less sensitive, more tough, less weird, more cool, less him, things would be easier. But how much can Isaiah keep inside until he shatters wide open?